Konsep Pendidikan Ketamadunan Pengakap (The Scouting Civilization Education) - Harry Ramza; Afri Yordan; Sofiyahna Kubro; Kaharudin Mokmin; Rusmiati Harun; Aslinda Aslinda (Penerbit Kemala Indonesia, 2015)
The Educational Scouting Civilization is an educational process based on scout education which aims to improve the living conditions of civilization or society outwardly and spiritually. In Arabic, the meaning of civilization as same as